SIAPIK PELATIHAN PENGELOLAAN KEUANGAN BERBASIS APLIKASI SI-APIK BAGI PELAKU USAHA PETANI GARAM DI DESA KETEWEL - Ni Komang Ayu Arya Widiastuti; Sang Ayu Putu Arie Indraswarawati; I Wayan Kusuma Wijaya; Kadek Suparsa Dana; I Gusti Agung Kadek Rai Mertayasa (Dharma Bhakti, 2023)
Loloan salt farmers in Ketewel village are a small business consisting of six people whose production focus is making salt through processing local resources. Salt farmers' knowledge of digital-based financial management is still low. Farmers often use income from sales of salt for personal needs. This will certainly have an impact on unstable cash flow in the business. To reduce the occurrence of unstable cash flows, daily financial recording must be carried out using currently available technology. The role of technology in financial processes is to reduce human errors and increase efficiency, assist inventory management processes, increase data accessibility and security, speed up payment processes and income tracking, and optimize expenses and reduce operational costs. The method used in this village project is in the form of discussions and providing training to salt farmers regarding digitalization-based financial management. The results of this village project activity were able to increase salt farmers' knowledge regarding digitized financial management which includes how to record business through the SI-APIK application. Keywords: Financial Management ; SIAPIK ; Salt Farmers ; Desa Ketewel